Prototype of a Multi-Robot System for Autonomous Gas Mapping in Polluted Environments (Hungarian Journal of Industry and Chemistry, 2011)
The need of environmental monitoring robots is imposed by nowadays trends related to sustainability – towards protecting the environment and the human factor. This research received a great amount of focus in the past years. The directions of study in this area of research will be overviewed in the next lines. They are varied and range from robots designed to monitor ammonia pollution near animal farms to robots which search for unexploded ordinance, or sources of leaks from pipes and tanks, and even to a collecting and segregating garbage robot which also monitors pollution while performing its other tasks. This paper describes a novel system that aims to explore dangerous sites (old mines, chemical plants, etc), where an autonomous ground robot and a micro unmanned aerial vehicle (UAV) are sent together to map the area in order to detect toxic gases. The new approach proposes a multi-robot architecture which uses a multi-sensor gas detection measurement unit which uses a Simultaneous Localization and Mapping (SLAM) algorithm for 3D autonomous gas mapping. Current research is trying to shift the use of robots for gas detection from indoor environments towards the outdoors. There can be found several research directions with applications based on ecological robots.